Heterolayered Carbonized MXene/Polyimide Aerogel for Low-Reflection Electromagnetic Interference Shielding and Multi-Spectrum Compatible Protection - Zhang, Shan; Liang, Chen‑Ming; Zhou, Lu; Wu, Juntao; Koo, Martin C.; Wu, Zongxin; Chen, Yun‑Tian; Wang, Guang‑Sheng (Nano-Micro Letters, 2026)
The advancement of next-generation high-frequency communication systems and stealth detection technologies necessitate the development of efficient, multi-spectrum compatible shielding materials. However, the achievement of simultaneous high efficiency and low reflectivity across microwave, terahertz, and infrared spectra remains a formidable challenge. Herein, a carbonized MXene/polyimide (C-MXene/PI) aerogel material integrating a spatially coupled hierarchically anisotropic structure with stepwise conductivity gradients was constructed. Electromagnetic waves propagate through the top-down vertical disordered horizontal architecture and progressive conductivity gradient of C-MXene/PI aerogel, undergoing stepwise absorption–dissipation–re-dissipation processes. The C-MXene/PI aerogel exhibits an average electromagnetic interference (EMI) shielding effectiveness of 91.0 dB in X-band and a reflection coefficient of 0.40. In the terahertz frequency band, the average EMI shielding performance reaches 66.2 dB with a reflection coefficient of 0.33. Furthermore, the heterolayered porous architecture of C-MXene/PI aerogels exhibits low thermal conductivity and reduced infrared emissivity, enabling exceptional infrared stealth capability across the 2–16 μm wavelength spectrum. This study provides an feasible strategy for constructing low-reflectivity multi-spectrum compatible shielding materials. Highlights: 1 A carbonized MXene/polyimide (C-MXene/PI) aerogel with hierarchically anisotropic and gradient electrical conductivity structures was constructed via a stepwise freezing strategy. 2 The C-MXene/PI aerogel shows a high EMI shielding effectiveness of 91.0 dB with a low reflection coefficient of 0.40 in the X-band, alongside a high shielding of 66.2 dB with an excellent low reflection of 0.33 in the THz band. 3 The C-MXene/PI aerogel exhibits low thermal conductivity and reduced infrared emissivity, enabling exceptional infrared stealth capability across the 2–16 μm wavelength spectrum.